ANALYSIS OF THE EFFECT OF HUMAN DEVELOPMENT INDEX, UNEMPLOYMENT RATE, AND INVESTMENT ON ECONOMIC GROWTH IN BALI PROVINCE - Kadek Dea Kristina Dewi; Surya Dewi Rustariyuni (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The economic growth of Bali Province has experienced significant fluctuations due to the impact of the COVID-19 pandemic, which affected the tourism, employment, and investment sectors. This study aims to analyze the influence of the Human Development Index (HDI), unemployment rate, and investment on the economic growth of Bali Province. The analytical method used in this research is multiple linear regression analysis. The findings reveal that HDI, unemployment rate, and investment simultaneously have a significant effect on economic growth in Bali Province. Partially, HDI and investment have a positive and significant effect on economic growth, whereas the unemployment rate has a negative but statistically insignificant effect. These findings indicate that improving human capital quality and increasing investment play a crucial role in fostering Bali's economic growth. Conversely, although the unemployment rate negatively affects economic growth, the impact is not statistically strong enough to influence growth directly.